Assessment of bone dysplasia by micro‐CT and glycosaminoglycan levels in mouse models for mucopolysaccharidosis type I, IIIA, IVA, and VII. Issue 2 (13th September 2012) - Rowan, Daniel J.; Tomatsu, Shunji; Grubb, Jeffrey H.; Montaño, Adriana M.; Sly, William S.
Abstract: Mucopolysaccharidoses (MPS) are a group of lysosomal storage diseases caused by mutations in lysosomal enzymes involved in degradation of glycosaminoglycans (GAGs). Patients with MPS grow poorly and become physically disabled due to systemic bone disease. While many of the major skeletal effects in mouse models for MPS have been described, no detailed analysis that compares GAGs levels and characteristics of bone by micro‐CT has been done. The aims of this study were to assess severity of bone dysplasia among four MPS mouse models (MPS I, IIIA, IVA and VII), to determine the relationship between severity of bone dysplasia and serum keratan sulfate (KS) and heparan sulfate (HS) levels in those models, and to explore the mechanism of KS elevation in MPS I, IIIA, and VII mouse models. Clinically, MPS VII mice had the most severe bone pathology; however, MPS I and IVA mice also showed skeletal pathology. MPS I and VII mice showed severe bone dysplasia, higher bone mineral density, narrowed spinal canal, and shorter sclerotic bones by micro‐CT and radiographs. Serum KS and HS levels were elevated in MPS I, IIIA, and VII mice. Severity of skeletal disease displayed by micro‐CT, radiographs and histopathology correlated with the level of KS elevation. We showed that elevated HS levels in MPS mouse models could inhibit N‐acetylgalactosamine‐6‐sulfate sulfatase enzyme. These studies suggest that KS could be released from chondrocytes affected by accumulation of other GAGs and that KS could be useful as a biomarker for severity of bone dysplasia in MPS disorders.